Comparison between PFC and PID control systems for a pneumatic cylinder. Issue 5 (15th May 2015) - Hashimoto, Yusuke; Satoh, Toshiyuki; Nagase, Jun‐Ya; Saga, Norihiko
<x xml:space="preserve">Abstract</x> The world population is aging, along with a decrease in population and a shortage of young workers. Mechanisms using pneumatic cylinders are therefore expected to be useful to perform tasks such as day‐to‐day work support for elderly people. However, a pneumatic cylinder involves a large time delay. Therefore, a traditional control system becomes complex, with the necessity to add Smith compensation. Therefore, we use predictive functional control (PFC). This control system is not complex even if the plant includes a time delay. This study evaluates the performance of force and position control systems using a pneumatic cylinder and PFC. We compare the PFC scheme with the proportional integral derivative (PID) control and show that PFC achieves better performance than PID control. © 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.